الزوائد في الأفعال في اللغة العربية واللغة الإندونيسية دراسة تقابلية تطبيقية - Hasna Muthi Mufidah; Nofa Isman (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2020)
This study aims to determine the affixes of verbs in arabic and indonesian language to find out the similiarates of two language from morphological, grammatical, and semantic aspects. And predict the diffuculties that faced by students. And prepare the learning materials that are appropriate for arabic language student in affixing araic and indonesia verbs based on the result of research. Thus study has reached the following results: first; they are 17 similarities and 69 differences between the arabic and indonesian language interms of morphology, grammatical and semantic, including changing the letters of the increase to six forms in the indonesian language, the triple verb that may be necessary exceeds its object, the terms have no special terms in the indonesian language, secondly; the existence of the expected obstacles due to the difference between the two languages, and the third; the application of a reciprocal study at the level of verbs plus in preparing an educational subject for indonesian learnes.